Behaviour of plasma citrulline after bariatric surgery in the BARIASPERM cohort. Issue 2 (February 2021) - Mifsud, François; Czernichow, Sébastien; Carette, Claire; Levy, Rachel; Ravaud, Philippe; Cynober, Luc; Neveux, Nathalie; Rives-Lange, Claire; ,; Eustache, F.; Coupaye, M.; Msika, S.; et al.
Summary: Background: Plasma citrulline is currently used in clinical practice as a marker of small bowel functional mass. Behaviour of plasma citrulline after bariatric surgery and its link with post-operative outcome are still poorly understood. Objective: Primary objective was to compare plasma citrulline 12 months after two types of bariatric surgery with pre-operative concentrations. Secondary objectives were to search for correlation between plasma citrulline variation and body weight and fat mass loss. Design: This is an ancillary study of the BARIASPERM study. Forty-six adult men (mean age 38.9 ± 7.9 years) who underwent gastric bypass (GB, n = 20) or sleeve gastrectomy (SG, n = 26) were included in this prospective study. Plasma citrulline was measured at baseline, 6 months and 12 months after surgery, as well as total body weight and fat mass measured by dual x-ray absorptiometry (DEXA). Results: Plasma citrulline increased significantly 12 months after surgery, both after gastric bypass and sleeve gastrectomy (respectively 30.2% [18.3–42.2] and 17.8% [5.8–29.7]). The increase was significantly higher after GB than after SG (p = 0.02) while total body weight and fat mass loss were not significantly different between GB and SG. The increase in plasma citrulline levels tended to be positively correlated with both weight and fat mass loss however the association did not reach statistical significance (p = 0.07 and p = 0.06 respectively). Conclusion: These results confirm the increase in plasma citrulline after GB published in two previous small studies. Citrulline also significantly increased after SG, and in spite of similar weight loss obtained with both surgery types, citrulline increase was higher after GB than SG. This suggests different modifications of intestinal functional mass after these two different techniques.